REPRESENTING OF THE ZAINICHI GROUP IN KOGONADA’S “PACHINKO”: STUART HALL'S READING - Dyah Lukita Wardhani; Saraswati Sakariah, Dewi (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study analyzes how the Zainichi Korean community is represented in Kogonada’s Pachinko through Stuart Hall’s theory of representation. Using a qualitative content analysis of eight episodes from Pachinko Season 1, this research examines the portrayal of Zainichi identity, survival strategies, and power relations within Japanese society. The findings reveal three major representations: (1) Zainichi identity shaped by Japan’s colonial legacy and intergenerational trauma, (2) survival strategies developed through family solidarity, perseverance, and selective assimilation, and (3) Japan’s continuing dominance that perpetuates social marginalization of the Zainichi. This study contributes to media and cultural studies by providing a critical perspective on how Pachinko reconstructs historical memory and challenges dominant narratives of Korean minorities in Japan.